1996
DOI: 10.1042/bj3190823
|View full text |Cite
|
Sign up to set email alerts
|

The biochemical characterization of a novel non-haem-iron hydroxylamine oxidase from Paracoccus denitrificans GB17

Abstract: The characterization of the hydroxylamine oxidase from the heterotrophic nitrifier Paracoccus denitrificans GB17 indicates the enzyme to be entirely distinct from the hydroxylamine oxidase from the autotrophic nitrifier Nitrosomonas europaea. Hydroxylamine oxidase from P. denitrificans contains three to five non-haem, non-iron-sulphur iron atoms as prosthetic groups, predominantly co-ordinated by carboxylate ligands. The interaction of the enzyme with the electron-accepting proteins cytochrome C556 and pseudoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 15 publications
0
23
0
Order By: Relevance
“…However, in heterotrophs ammonia oxidation cannot support lithoautotrophic growth. One reason may be that oxidation of NH # OH by a periplasmic hydroxylamine oxidase requires oxygen rather than water (Moir et al, 1996 ;Richardson et al, 1998) and thus yields only two reducing equivalents. These can be transferred to either the nitrite reductase, nitrous oxide reductase or nitric oxide reductase, so that the nitrite produced can ultimately be reduced to N # (Fig.…”
Section: Multiple Physiological Roles For Normentioning
confidence: 99%
“…However, in heterotrophs ammonia oxidation cannot support lithoautotrophic growth. One reason may be that oxidation of NH # OH by a periplasmic hydroxylamine oxidase requires oxygen rather than water (Moir et al, 1996 ;Richardson et al, 1998) and thus yields only two reducing equivalents. These can be transferred to either the nitrite reductase, nitrous oxide reductase or nitric oxide reductase, so that the nitrite produced can ultimately be reduced to N # (Fig.…”
Section: Multiple Physiological Roles For Normentioning
confidence: 99%
“…The images on the right are rotated by 90°with respect to those on the left, so the proposed electron entry site is facing the reader. The images were prepared using the USCF Chimera program [35] b electrostatic character has also been suggested for other electron transfer complexes involving pseudoazurin and/or cytochrome c-550 from these organisms, and P. panthotropus cytochrome c peroxidase [48] and P. denitrificans non-heme-iron hydroxylamine oxidase [50].…”
Section: General Analysismentioning
confidence: 99%
“…It has been reported that HAOs are distinct from different organisms. HAO from P. denitrificans is a small periplasmic monomer (20-kDa) containing ferric iron [21], while the enzyme from Pseudomonas PB16 is a homo-dimer of 68-kDa subunits with no detectable cofactors [22]. In the present study, hydroxylamine oxidoreductase gene was not identified.…”
Section: Resultsmentioning
confidence: 42%